Development of an Android-Based Tourism Application for Banyumas Regency using the Waterfall Model - Hananta, Arnelka; Prasetyo, Novian Adi; Arifa, Amalia Beladinna (Nusantara Journal of Artificial Intelligence and Information Systems, 2025)
Tourism is a key sector for regional economic growth and needs to be supported by the use of technology. This research aims to design and build an Android-based tourism application for Banyumas Regency using the Waterfall method. The application provides information on various tourist destinations, including nature, artificial attractions, culinary spots, and hotels. The development process followed the sequential stages of needs analysis, system design, implementation, testing, and maintenance. Unified Modeling Language (UML) diagrams were used for system modeling, while Android Studio and Firebase Firestore served as the main development tools. System functionality was validated through Blackbox Testing, while usability was assessed using the System Usability Scale (SUS) method. The application successfully passed functionality tests across multiple smartphone models and achieved an average SUS score of 84.83, indicating excellent usability. The research concludes that the tourism application effectively assists users in finding tourism information in Banyumas Regency. Future improvements are suggested by adding features such as distance-based recommendations and advanced search functions to enhance user experience.